Impacts of indoor radon on health: a comprehensive review on causes, assessment and remediation strategies - Nunes, Leonel J. L. (2022)
Indoor radon exposure is raising concerns due to its impact on health, namely its known relationship with lung cancer. Consequently, there is an urgent need to understand the risk factors associated with radon exposure, and how this can be harmful to the health of exposed populations. This article presents a comprehensive review of studies indicating a correlation between indoor radon exposure and the higher probability of occurrence of health problems in exposed populations. The analyzed studies statistically justify this correlation between exposure to indoor radon and the incidence of lung diseases in regions where concentrations are particularly high. However, some studies also showed that even in situations where indoor radon concentrations are lower, can be found a tendency, albeit smaller, for the occurrence of negative impacts on lung cancer incidence. Lastly, regarding risk remediation, an analysis has been conducted and presented in two core perspectives: (i) focusing on the identification and application of corrective measures in pre-existing buildings, and (ii) focusing on the implementation of preventive measures during the project design and before construction, both focusing on mitigating negative impacts of indoor radon exposure on the health of populations.